When the law influences medical practice: Potential impact of the Bouchard-Lebrun ruling on the forensic unit of the Malartic Psychiatric Hospital in Northern Quebec, Canada. (May 2021) - Laliberté, Vincent; Aird, Maxine; Gilbert Tremblay, Ugo; Gendron, Sébastien
Abstract: The attribution of criminal responsibility in the context of substance intoxication is a matter of controversy in forensic psychiatry. In 2011, the Supreme Court of Canada ruled that Tommy Bouchard-Lebrun was guilty in the straightforward case of a crime committed while in a state of substance-induced psychosis by an individual without a history of mental disorder. However, the ruling may since have served as a precedent also for settling cases where an offence is committed while in a certain state of intoxication and where there is much more diagnostic uncertainty. The goal of our research was to study the impact of the Bouchard-Lebrun Supreme Court decision on rates of criminal responsibility judgements and toxic psychosis diagnosis in the context of such cases. Applying a time-trend ecological study design, we conducted a chart review of every patient treated at the forensic unit of the Malartic Psychiatric Hospital in northern Quebec in the short periods pre- and post-ruling. We then determined the proportion of patients judged not criminally responsible and the proportion diagnosed with substance-induced psychosis. We ran chi-squared tests on the two sets of dichotomous variables. In the period following the Bouchard-Lebrun ruling, a statistically significant decrease was observed in the proportion of individuals judged not criminally responsible, as was a statistically significant increase in the proportion of individuals diagnosed with substance-induced psychosis. The findings suggest that the Bouchard-Lebrun ruling may have had an impact on subsequent forensic psychiatry decision-making and treatment at the Malartic Hospital.